2021
DOI: 10.1038/s41598-021-03809-4
|View full text |Cite
|
Sign up to set email alerts
|

High diversity of small insectivorous mammals on Qinghai–Tibet Plateau and first description of karyotype for four endemics of China

Abstract: Among seven species of the order Eulipotyphla (from southern Gansu and northern Sichuan Provinces, Central China) studied cytogenetically, karyotypes of one talpid species, Uropsilus aff. soricipes (2n = 36, NFa = 54), and three soricid species, Chodsigoa hypsibia (2n = 65, NFa = 66), Sorex cansulus (2n = 42, NFa = 64) and Sorex thibetanus (2n = 42, NFa = 60), are described cytogenetically for the first time. All four species are endemic to China with distribution ranges restricted to the Qinghai–Tibet Plateau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A review by Vujošević et al (2018) showed that the number of mammalian species with additional chromosomes is 85 (~ 1.9% of the karyotypically studied ones), and at least 60 of them are rodents, mostly from the superfamily Muroidea (Trifonov et al, 2010;Graphodatsky et al, 2011). In recent years, several new mammalian species -bats and insectivoreswere added into the category of B-carriers (Pavlova et al, 2021;Volleth et al, 2022;Rajičić et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A review by Vujošević et al (2018) showed that the number of mammalian species with additional chromosomes is 85 (~ 1.9% of the karyotypically studied ones), and at least 60 of them are rodents, mostly from the superfamily Muroidea (Trifonov et al, 2010;Graphodatsky et al, 2011). In recent years, several new mammalian species -bats and insectivoreswere added into the category of B-carriers (Pavlova et al, 2021;Volleth et al, 2022;Rajičić et al, 2022).…”
Section: Introductionmentioning
confidence: 99%